2019
DOI: 10.2147/lra.s191851
|View full text |Cite
|
Sign up to set email alerts
|

<p>Celiac plexus block as a diagnostic tool in suspected pediatric median arcuate ligament syndrome</p>

Abstract: We report the use of celiac plexus block (CPB) as a diagnostic aid in the evaluation of median arcuate ligament syndrome (MALS) in a pediatric patient. MALS is a rare cause of severe, debilitating, abdominal postprandial pain associated with nausea, vomiting, occasional diarrhea, unintentional weight loss, and abdominal bruit. MALS is a diagnosis of exclusion, after multiple investigations. This is the first case report where CPB was used to confirm candidacy for corrective surgery in the pediatric population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was reported that pain relief after celiac plexus block (CPB) had been found to be a predictor of symptomatic improvement after corrective surgery [ 14 ]. Some authors reported that CPB was useful to confirm candidacy for corrective surgery of MALS [ 15 , 16 ]. In these symptomatic MALS patients, MAL release with ganglionectomy of the celiac plexus might be the best treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that pain relief after celiac plexus block (CPB) had been found to be a predictor of symptomatic improvement after corrective surgery [ 14 ]. Some authors reported that CPB was useful to confirm candidacy for corrective surgery of MALS [ 15 , 16 ]. In these symptomatic MALS patients, MAL release with ganglionectomy of the celiac plexus might be the best treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the incidence of MALS is estimated at approximately two per every 100,000 patients 10. The majority of MALS patients are relatively young women between the ages of 20–50 years old with thin body habitus who have been extensively worked up for various intra-abdominal pathology 1,6.…”
Section: Discussionmentioning
confidence: 99%
“…Once other causes have been ruled out, the diagnosis can be confirmed with imaging including duplex ultrasound, CT angiography, and magnetic resonance angiography revealing compression or stenosis of the celiac artery 6,8. Percutaneous diagnostic celiac ganglion blockade, in which lidocaine is injected into splanchnic nerves feeding into the celiac plexus, can also be performed by general surgery or IR to predict symptomatic improvement with surgical intervention 1012…”
Section: Discussionmentioning
confidence: 99%
“…Median arcuate ligament syndrome (MALS) is a rare (2/100,000) entity characterized by severe, debilitating, postprandial epigastric pain associated with a constellation of other vague symptoms including nausea, vomiting, occasional diarrhea, and abdominal bruit. and/or weight loss, and even leads to an abnormal aversion to food, "sitophobia" [1,2]. The classic triad of abdominal pain related to meals, weight loss, and abdominal bruit may not always present.…”
Section: Introductionmentioning
confidence: 99%